Spatiotemporal pattern of landscape ecological risk in the Yangtze River Basin and its influence on NPP - Jia, Lu; Yu, Kunxia; Li, Zhanbin; Li, Peng; Cong, Peijuan; Li, Binbin (Frontiers in Forests and Global Change, 2024)
The rapid development of the social economy and the continuous change of land use have greatly altered the ecological risk of the regional landscape. This research focused on the Yangtze River Basin in China and aimed to examine the temporal and spatial variation characteristics of landscape ecological risk (LER) over a period of 34 years (1982-2015), after determining the optimal sub-watershed scale. And based on the conditional probability framework, the nonlinear response of NPP to LER was revealed. Finally, the primary driving factors of LER were explored and additional potential causes for changes in NPP were discussed. The study findings indicated that the mean annual LER of the Yangtze River Basin exhibited a spatial distribution characterized by high values observed in the western regions and low values in the eastern regions at the optimal sub-basin scale. Specifically, 30.56 % and 22.22 % of the sub-basins demonstrated a significant upward and downward trend in annual LER, respectively (P<0.05). The spatial distribution pattern of the mean annual NPP demonstrated high values in the middle region and low values in the western area, with annual NPP significant increasing in 94.44% of the sub-basins (P<0.05). The relationship between annual NPP and annual LER was found to be nonlinear, indicating that higher annual LER result in higher probability of median and high values of annual NPP from the perspective of watershed average. Furthermore, climate factors emerged as the main influencing factor of NPP. Based on these discoveries, upcoming endeavors should concentrate on optimizing landscape formations, and executing a judicious distribution of plant species.